2017
DOI: 10.3390/molecules22071080
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Cytotoxicity of Gemcitabine-Functionalized Magnetite Nanoparticles

Abstract: Nanotechnology has been successfully used for the fabrication of targeted anti-cancer drug carriers. This study aimed to obtain Fe3O4 nanoparticles functionalized with Gemcitabine to improve the cytotoxic effects of the chemotherapeutic substance on cancer cells. The (un) functionalized magnetite nanoparticles were synthesized using a modified co-precipitation method. The nanoconjugate characterization was performed by XRD, SEM, SAED and HRTEM; the functionalizing of magnetite with anti-tumor substances has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 68 publications
(77 reference statements)
1
26
0
1
Order By: Relevance
“…More importantly AuNPs-chemotherapeutic conjugate, in some cases, were more effective than chemotherapeutic alone. We compared the cytotoxicity of chemotherapeutics on cell lines used in this study (143B, PANC-1, MCF7) with literature data, and generally, we had similar results [31,32,41,42,[33][34][35][36][37][38][39][40]. For DOX, Kamba et al, reported that IC50 was around 0.5µg/mL (MG63, osteosarcoma cells), Yui et al, showed that IC 50 was approximately equal 2 µg/mL (PANC1 cells).…”
Section: Discussionsupporting
confidence: 65%
“…More importantly AuNPs-chemotherapeutic conjugate, in some cases, were more effective than chemotherapeutic alone. We compared the cytotoxicity of chemotherapeutics on cell lines used in this study (143B, PANC-1, MCF7) with literature data, and generally, we had similar results [31,32,41,42,[33][34][35][36][37][38][39][40]. For DOX, Kamba et al, reported that IC50 was around 0.5µg/mL (MG63, osteosarcoma cells), Yui et al, showed that IC 50 was approximately equal 2 µg/mL (PANC1 cells).…”
Section: Discussionsupporting
confidence: 65%
“…The bare iron oxide nanoparticles have been synthesized ( Supplementary Information, Section S1.1 ) using a modified chemical co-precipitation method, as in Popescu et al [ 18 ], which implied a 1.65:1 Fe 3+ :Fe 2+ ratio, in order to compensate the oxidation of Fe 2+ [ 20 , 21 ]. The biocompatibility of bare Fe 3 O 4 nanoparticles (NP) was proven by our in vitro data on cyto- and geno-toxicity ( Supplementary Information, Section S2.2 and Figure 2 H), confirming other reports [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…To test our hypothesis, mechanistic investigation concerning the effect of ionizing radiation on the internalization and cytotoxicity of NP-DOX have been performed in a MG-63 human osteosarcoma cell model. We synthesized the nanoparticles (as described in Popescu et al [ 18 ]) and then characterized them using relevant physico-chemical methods ( Supplementary Materials Sections S1.1 and S2.1 ). In vitro testing on MG-63 cells revealed information on the internalization, cyto- and geno-toxicity of NP-DOX and have been used to select the experimental conditions, concentrations and observation time points for the investigations we report here ( Supplementary Materials Section S2.2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The general side effects include bone marrow suppression, liver and kidney problems, nausea, fever, rash, shortness of breath and hair loss [31][32][33][34]. Therefore, for today, the possibility is actively studied to use GC in composition of magnetically sensitive NC and ML on their basis to create multi-functional antitumor medicines for targeted delivery and local therapy [35][36][37][38].…”
Section: Experimental Part and Discussionmentioning
confidence: 99%